INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, KNOWLEDGE MANAGEMENT AND QUALITY OF WORK LIFE ON PERFORMANCE EMPLOYEE: (Empirical Study Using Survey Methods and Path Analysis on Employees Shoe Pad Industry in Greater Tangerang) - Setiawan, Temmy; Moeins, Anoesyirwan; Yusnita, Nancy (Journal of Industrial Engineering & Management Research, 2024)
The aim of this research is to determine and analyze the influence of To analyze the magnitude of the direct influence of transformational leadership on performance employees, knowledge management on employee performance, quality of work life on employee performance, transformational leadership on the quality of work life knowledge management on the quality of work life and to analyze its magnitude the indirect influence of transformational leadership on employee performance through quality of work life and knowledge management on employee performance through quality of work life.. The population in this study was 111,283 people, with sample determination based on the maximum likelihood method (Maximum Likelihood Estimate) with a sample size of 200 respondents. The research method used in this research uses research methods quantitative. The research design uses explanatory research and descriptive research through an approach surveys and questionnaires. The analysis used in this research is factor analysis confirmatory (Confirmatory Factor Analysis/ CFA). The statistical analysis tool used is LISREL 8.70. Based on the research results, the following research findings on leadership were obtained transformational has a positive and significant effect on employee performance. Knowledge management has a positive and insignificant effect on employee performance and quality of life work has a positive and significant effect on employee performance. leadership transformational has a positive and significant effect on the quality of work life. Knowledge management has a positive effect on the quality of work life and leadership transformational has a positive and significant effect on employee performance through quality work life and knowledge management have a positive effect on employee performance through quality of work life. Based on the results of calculating direct and indirect effects shows that the influence of the mediator variable in this research is fully mediating. This means that the quality of work life variable can be said to be a mediating variable for all exogenous variables in this study are due to the quality of work life entirely acts as a mediating variable that determines the increase in employee performance.